Reducing the Need for Repeat Urine Drug Testing with the Gray Zone Determined by the Measurement Uncertainty: Gray Zone for Urine Drug Testing - Huysal, Kagan; Üstündağ, Yasemin; Çağlak, Hatice Azra; Yeşil, Meryem Rümeysa (Journal of Medical Biochemistry, 2023)
BackgroundOn an initial urine screening test for illegal substances, if the concentration of a substance is at or above the determined legislative threshold, it is reported as positive. Repeat testing with the same sample to verify before reporting is a common practice of clinical laboratories. This study aimed to determine whether measurement uncertainty (MU) results can be used to detect a gray zone to reduce repeat testing.Materials and MethodsA retrospective study using data from … ….. …… ……. laboratory information system between 1.January.2020 and 1.July.2022 was conducted. The MU values for urinary amphetamine, cannabinoid, cocaine, and opioid parameters using ADVIA Chemistry reagents (Siemens Healthcare Diagnostic Inc., Germany) on a Siemens ADVIA 1800 chemical analyzer were calculated. The gray zone was defined as the cut-off value ± MU. Samples that were studied twice within one hour before reporting for the same urine sample were analyzed.ResultsFrom a total of 31,839 patients’ (16–65 years), urine samples, 319 amphetamine, 198 cannabinoid, 112 cocaine, and 125 opiate tests were repeated. Mean biases between the repeat test results were -7.64 (95% CI: −13.71 to -1.57) for the amphetamine and 1.16 (95% CI: 0.31 to 2.01) for the cannabinoid results. Ten amphetamine, 12 cannabinoid and 2 cocaine test results changed from positive to negative or negative to positive on retesting, all within the gray zone level defined by the MU value. ConclusionsIt is necessary to define the gray zone around the cut-off value for each illicit substance based on its MU for repeat testing.
Keywords: cut-off; gray zone; measurement uncertainty; amphetamine; cannabinoid; cocaine